US lung cancer trends by histologic type. Issue 18 (11th August 2014) - Lewis, Denise Riedel; Check, David P.; Caporaso, Neil E.; Travis, William D.; Devesa, Susan S.
Abstract : BACKGROUND: Lung cancer incidence rates overall are declining in the United States. This study investigated the trends by histologic type and demographic characteristics. METHODS: Surveillance, Epidemiology, and End Results (SEER) program rates of microscopically confirmed lung cancer overall and squamous cell, small cell, adenocarcinoma, large cell, other, and unspecified carcinomas among US whites and blacks diagnosed from 1977 to 2010 and white non‐Hispanics, Asian/Pacific Islanders, and white Hispanics diagnosed from 1992 to 2010 were analyzed by sex and age. RESULTS: Squamous and small cell carcinoma rates declined since the 1990s, although less rapidly among females than males. Adenocarcinoma rates decreased among males and only through 2005, after which they then rose during 2006 to 2010 among every racial/ethnic/sex group; rates for unspecified type declined. Male/female rate ratios declined among whites and blacks more than among other groups. Recent rates among young females were higher than among males for adenocarcinoma among all racial/ethnic groups and for other specified carcinomas among whites. CONCLUSIONS: US lung cancer trends vary by sex, histologic type, racial/ethnic group, and age, reflecting historical cigarette smoking rates, duration, cessation, cigarette composition, and exposure to other carcinogens. Substantial excesses among males have diminished and higher rates of adenocarcinoma among young females have emerged as rates among males declined more rapidly. The recognition of EGFR mutation and ALK rearrangements that occur primarily in adenocarcinomas are the primary basis for the molecular revolution that has transformed lung cancer diagnosis and treatment over the past decade, and these changes have affected recent type‐specific trends. Cancer 2014;120:2883–2892. © 2014 American Cancer Society . Abstract : This analysis of lung cancer trends by histologic type represents a fresh classification of lung cancer histology and reveals several new incidence trends by sex and race/ethnicity. This new analysis by histologic type is important in the context of molecular‐based diagnosis and should inform additional research that will direct therapy appropriate to the specific lung cancer type.